2001
DOI: 10.1073/pnas.191369098
|View full text |Cite
|
Sign up to set email alerts
|

Opposing cardioprotective actions and parallel hypertrophic effects of δPKC and ɛPKC

Abstract: Conflicting roles for protein kinase C (PKC) isozymes in cardiac disease have been reported. Here, ␦PKC-selective activator and inhibitor peptides were designed rationally, based on molecular modeling and structural homology analyses. Together with previously identified activator and inhibitor peptides of PKC, ␦PKC peptides were used to identify cardiac functions of these isozymes. In isolated cardiomyocytes, perfused hearts, and transgenic mice, ␦PKC and PKC had opposing actions on protection from ischemiaind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
464
2
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 506 publications
(499 citation statements)
references
References 36 publications
22
464
2
5
Order By: Relevance
“…Indeed, it is known that up regulation of PKC-d is associated with the development of metastasis (see Debies & Welch 34 ). Activation of PKC-e is known to participate in the cardioprotective effects of preconditioning 35 while PKC-d is involved in the deleterious effects of ischaemia 36 . We observed that both PKC isoforms were less translocated to the particulate fraction in the fish oil diet group but this decrease was more pronounced for PKC-d than for PKC-e.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is known that up regulation of PKC-d is associated with the development of metastasis (see Debies & Welch 34 ). Activation of PKC-e is known to participate in the cardioprotective effects of preconditioning 35 while PKC-d is involved in the deleterious effects of ischaemia 36 . We observed that both PKC isoforms were less translocated to the particulate fraction in the fish oil diet group but this decrease was more pronounced for PKC-d than for PKC-e.…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal injection of the dPKC-selective activator, cdRACK (Chen et al, 2001), after CCA release partially reversed the protective effect of hypothermia at 24 h ( Figure 9B). …”
Section: Partially Reverses the Protective Effect Of Hypothermiamentioning
confidence: 94%
“…LDH assay kit was from Roche Molecular Biotechnology (Indianapolis, USA). The δPKC-specific antagonist peptide, δV1-1 (δPKC inhibitor, amino acids 8-17 [SFNSYELGSL]) was synthesized by American Peptides and conjugated to TAT-carrier peptide (amino acids 47-57) via a cysteine-cysteine S-S bond at their N termini, as previously described [14].…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-four hours later, fresh serum-free medium was added and the myocytes were treated with tunicamycin as indicated in the figures. The δPKC-selective antagonist peptide, δV1-1, was conjugated to the TAT 47-57 carrier peptide for transmembrane delivery [14]. The unconjugated TAT 47-57 carrier peptide was used as a control.…”
Section: Isolation Of Rat Neonatal Cardiac Myocytesmentioning
confidence: 99%
See 1 more Smart Citation